Meditation and its benefits - Wójcik, Magdalena; Boreński, Grzegorz; Poleszak, Julita; Szabat, Przemysław; Szabat, Marta; Milanowska, Joanna (Journal of Education, Health and Sport, 2019)
Introduction: Meditation can include any kind of practices during practitioners can calm their mind and expend their consciousness. Meditation practising have been known since a long time ago. However, in the West it is still gaining popularity since nowadays people are under more and more stress. Meditation is thought to be helpful in coping with chronic disorders or stress. The aim of the study: The purpose of this systemic review was to collect and analyse available data about practising meditation and its effects on health. Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed database was carried out using the following keywords: meditation, stress, health. Description of the state of knowledge: Psychological stress contributes to the development of many disorders. Studies of the effects of meditation practises such as mindfulness meditation or yoga showed that they are beneficial for reducing stress, depression and anxiety. The study in which participated patients with active depression and anxiety showed a reduction of both depression and anxiety score after the course meditation comparing to control group. Yoga practising was also examined in many studies as a depression treatment and showed some promising results. Another study showed improvement in perceived stress after yoga practising on a group of distressed women. Summary: Many studies of meditation practises showed their beneficial effects on depression, mood, anxiety and stress. People should be more aware of the effects of practises such as mindfulness meditation or yoga and consider their role in addressing psychological stress. Meditation may be a useful practise in maintaining health and well-being. However, further researches of meditation practises are still needed.